The role of attachment styles in regulating the effects of dopamine on the behavior of salespersons - Verbeke, Willem J.; Bagozzi, Richard P.; van den Berg, Wouter (Frontiers in Human Neuroscience, 2014)
Two classic strategic orientations have been found to pervade the behavior of modern salespersons: a sales orientation where salespersons use deception or guile to get customers to buy even if they do not need a product, and a customer orientation where salespersons first attempt to discover the customer’s needs and adjust their product and selling approach to meet those needs. Study 1 replicates recent research and finds that the Taq A1 variant of the DRD2 gene is not related to either sales or customer orientation, whereas the 7-repeat variant of the DRD4 gene is related to customer orientation but not sales orientation. Study 2 investigates gene × phenotype explanations of orientation of salespersons, drawing upon recent research in molecular genetics and biological/psychological attachment theory. The findings show that attachment style regulates the effects of DRD2 on customer orientation, such that greater avoidant attachment styles lead to higher customer orientation for persons with the A2/A2 variant but neither the A1/A2 nor A1/A1 variants. Likewise, attachment style regulates the effects of DRD4 on customer orientation, such that greater avoidant attachment styles lead to higher customer orientation for persons with the 7-repeat variant but not other variants. No effects were found on a sales orientation, and secure and anxious attachment styles did not function as moderators.